Economic Optimization through the Development of Family-Based Micro Businesses in the Padangmatinggi I Village Environment, Padangsidimpuan City - Kholidah Hannum Hasibuan; Yusrina Gultom; Silvia Anggraini Hsb; Reyhan Hidayat; Zulhimma Zulhimma (International Journal of Economics, Commerce, and Management, 2026)
Strengthening family-based microenterprises is one strategic approach to improving the economic resilience and independence of local communities. Family microenterprises not only serve as a source of income, but also as an important instrument in maintaining the social and economic stability of households. This study aims to describe the conditions of family-based microenterprises, identify obstacles to their development, and formulate strategies for optimizing family economics in Neighborhood I of Padangmatinggi Village, Padangsidimpuan City. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation studies. Research informants include family micro-business actors, village officials, and other related parties. The results show that family-based micro-businesses have a real contribution to increasing household income and meeting basic family needs. However, business development still faces limitations in capital, low financial literacy, limited product innovation, and minimal marketing access. Therefore, an integrated development strategy is needed that includes increasing human resource capacity, facilitating access to financing, utilizing digital technology, and institutional support from the local government to realize the sustainability of family micro-businesses.